Sucrose and Maltose as Carbon Sources for Fermentative Production of Polysaccharide by Aspergillus niger van tiegh. - S. Murugesan, N. Senthilkumar* and (Recent Research in Science and Technology, 2010)
Two carbon sources viz., sucrose and maltose were used to induce extracellular polysaccharide production in Aspergillus niger. Maximum production of polysaccharide 513 mg/100ml of culture filtrate was observed at pH 7, 10% sucrose concentration, 15 days of incubation. Polysaccharide production was increased with increase in growth of mycelium of A. niger in both the substrates. The optimum pH and incubation periods for the maximum production of polysaccharide were pH 7 and 15 days respectively. The polysaccharide produced by A. niger was the polyol of 3,4,6 tri-o-methyl D glucose with b-1-3 glycosidic linkage commonly known as glucan. The polysaccharide produced by this species may be composed of glucose and little amount of galactose and other oligosaccharides. Polarimetric studies revealed that the fractions containing glucose gave laevorotatory values of the optical rotation.